Les constellations narratives. Que font les téléspectateurs des adaptations multimédiatiques des séries télévisées ? - Sarah Sepulchre (TV Series, 2013)
TV shows go further and further beyond the small screen to invest in other media, such as books, the internet, cinema, and games. We call “constellations” these sets of elements that seem to participate in the same story. The first part of the article shows that this notion is similar to that of “transmedia” (Henry Jenkins). What seems to be at the heart of these narrative systems is the creation of immersive diegetic worlds (Anne Besson). The second part of the contribution develops the notion of immersion (Renée Bourassa, Jean-Marie Schaeffer) and of figure (Bertrand Gervais), which allow us to conceptualize readers’ practices. A study of exploratory reception based on semi-directive interviews with fans of TV series concludes the article. It shows that consumers take pleasure in prolonging the pleasure of the diegetic world by a more fictional than technical immersion. On the other hand, the elements that fuel the universe are not always fictional in nature, because the readers occasionally use information on the actors and the places from the story to nourish their imaginative activity. The constellations remain, however, weak transmediatic stories, as the different entries are less autonomous than in the ideal cases described by Henry Jenkins. These narrative sets function on the basis of the satellite model presented by Richard Saint-Gelais. Finally, it appears that the consumption of the constellation is a true appropriation of the fictional universe by readers.